Aplicativo para ciclistas BIKESPOT - Oliveira, Fábio do Couto (Universidade do Vale do Rio dos Sinos, 2016)
This article has as the main purpose presenting an easy to use solution to provide information regarding about a bicycle culture in the city of Porto Alegre, RS, Brazil and also to provide a common environment for all the cyclists and everyone who wants to use a bicycle to commuting to their workplaces or just to share experiences among the safety places to ride a bike, to park their bikes or just suggest the places where the bicycles are welcome. This application is looking for to be a powerful tool to help and empower the bike community in the cities, especially for cyclists, but not only for them who usually use as transportation, but also for their quality time.
Keywords: Android; Computação móvel; Bicicleta; GPS; Mobilidade urbana; Aplicativos sociais; Mobile computing; Bicycle; Urban mobility; Social applications